A Simulation of Digital Device to Calculate Electrical Energy Usage Costs Based on Kwh Metres - Masri, Mahrizal; Alam, Hermansyah; Pelawi, Zulfadli (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2025)
The electricity payment system in Indonesia is by calculating the power used. The tool that records the use of electrical energy is a KWH meter. From this problem, an idea was obtained to record the KWH meter digitally so that we can easily find out how much electricity is used. This tool provides a value every time a pulse is detected by a photo diode against the KWH disc movement indicator. The function of this tool is a simulation with assumptions based on the KWH meter disc movement indicator detected by the photo diode, after which the pulses are processed on the AT89S51 microcontroller, and presented via a seven segment display. So that customers can easily find out the cost of electricity that has been used. Overall tool testing is done by connecting all parts of the tool and the KWH Meter is connected to the power grid and to the load. Simple testing is done by connecting the tool to a load of 100 watts and 200 watts